2011
DOI: 10.1007/s12678-011-0042-5
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the Electrocatalytic Activity of Gold Nanoparticles Towards Methanol Oxidation

Abstract: By citrate reduction of HAuCl 4 , Au nanoparticles with a diameter of 15 nm and low polydispersity were synthesized. By deposition and subsequent dissolution of PbO 2 in an alkaline medium, the particles were cleaned from their organic capping agents. The electrocatalytic behavior towards methanol oxidation under alkaline condition of these particles was found to be substantially enhanced by the cleaning procedure. The origin of the enhancement was studied by comparing the voltammetric profiles of the cleaned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…[42,43] Subsequently,t or emove the Pb/ PbO 2 after the electrochemical cleaning process, the supported particles were dipped in 0.1 m HNO 3 for 10 min. [45] Figure2B shows the blank voltammetric response of the Au nanoparticles after this cleaningp rocedure. As can be seen from the voltammograms, no peaks were observed between 0.25 and 0.8 V, which confirms the absence of residual Pb fromt he cleaningp rocedure.…”
Section: Characterization Of Preferentially Oriented Nanoparticlesmentioning
confidence: 99%
“…[42,43] Subsequently,t or emove the Pb/ PbO 2 after the electrochemical cleaning process, the supported particles were dipped in 0.1 m HNO 3 for 10 min. [45] Figure2B shows the blank voltammetric response of the Au nanoparticles after this cleaningp rocedure. As can be seen from the voltammograms, no peaks were observed between 0.25 and 0.8 V, which confirms the absence of residual Pb fromt he cleaningp rocedure.…”
Section: Characterization Of Preferentially Oriented Nanoparticlesmentioning
confidence: 99%
“…In electrocatalysis, the oxidation of organic molecules on a gold electrode material is not widely investigated like on platinum-based materials. However, some studies using smooth or supported gold-based materials were considered. Thus, during the last two decades, the oxidation of glucose was a keen interest since one can consider glucose as a renewable fuel in energy conversion systems. , Therefore, the electrocatalytic oxidation of glucose in alkaline medium was studied on Cu, Ag–Au, Ag, Pt and Au materials. ,, In these latter cases and in neutral medium, gold is an attractive electrode due to its catalytic activity at low potentials compared to the other catalysts in the same conditions. ,, …”
Section: Introductionmentioning
confidence: 99%
“…By scanning towards positive potentials, lead oxides are electrodeposited on the nanoparticle surface that protects the gold surface structure while promoting the oxidation of the capping agent. 9,10 Prior to ORR experiments gold nanoparticlemodified glassy carbon electrodes were cycled in 1 mM Pb(NO 3 ) 2 , 0.1 M NaOH solution from À0.73 V (vs. SCE) to +0.5 V with three cycles performed followed by a linear scan from À0.73 V (vs. SCE) to 0 V. Following this ''cleaning'' procedure, the nanostructured electrodes were rinsed with deionised water prior to ORR experiments.…”
Section: ''Cleaning'' Of the Gold Nanoparticle Surfacementioning
confidence: 99%
“…Thus, this might be related to the removal of the citrate layer but also to the presence of lead species on the nanoparticle surface after the deposition-stripping cycling. Indeed, Chen et al 9 found traces of lead after applying a similar cleaning treatment to gold nanoparticles.…”
Section: Gold Macroelectrode and Au-nps/gcementioning
confidence: 99%